2018
DOI: 10.1088/1755-1315/105/1/012087
|View full text |Cite
|
Sign up to set email alerts
|

Exergoeconomic analysis and optimization of a combined double flash – binary cycle for Ulubelu geothermal power plant in Indonesia

Abstract: Abstract. In this paper, the combination of double-flash and binary cycles for Ulubelu geothermal power plant is proposed and optimized by using the Matlab software. This proposed system uses real data and properties of brine exploited from the Ulubelu geothermal well in Indonesia and four working fluid candidates, namely n-Pentane, R141b, R123 and R245fa are used in binary cycles. Optimization using a multi-objective genetic algorithm with an exergoenomic approach is applied to find out the proposed system pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This value shows how much power can be produced with a certain heat input. Thermal efficiency can be calculated using the equation [15]:…”
Section: Efficiency Cycles Thermalmentioning
confidence: 99%
“…This value shows how much power can be produced with a certain heat input. Thermal efficiency can be calculated using the equation [15]:…”
Section: Efficiency Cycles Thermalmentioning
confidence: 99%
“…Their evaluation of the plant showed that in double flash energy and exergy efficiency were increased from 16.26% and 40.06% to 17.73% and 50.89%, respectively. Rachmat et al (2018) were conducted anexergoeconomic analysis and optimization of a combined double flash binary cycle for Ulubelu geothermal power plant in Indonesia. The proposed system was used current data and properties of brine exploited from the Ulubelu geothermal well in Indonesia and four working fluid candidates, namely n-Pentane, R141b, R123, and R245fa are used in binary cycles.…”
Section: Introductionmentioning
confidence: 99%